A Miniaturized Triple Band Monopole Antenna for WLAN and WiMAX Applications - Yingsong Li; Wenhua Yu (International Journal of Antennas and Propagation)
A miniaturized triple band monopole antenna with a small size is proposed and its performance is investigated both numerically and experimentally for worldwide interoperability for microwave access (WiMAX) and wireless local area network (WLAN) applications. The three resonance frequencies are realized by using a toothbrush-shaped patch (TSP), a meander line (ML), and an inverted U-shaped patch (IUSP). The center frequencies of the triple bands can be controlled by adjusting the dimensions of the TSP, ML, and IUSP. Simulated and measured results are presented to demonstrate that the proposed triband monopole antenna with a good impedance bandwidth and omnidirectional radiation patterns is well suitable for WLAN and WiMAX communication applications.